2018
DOI: 10.1111/chso.12310
|View full text |Cite
|
Sign up to set email alerts
|

Young Adult Carers: The Impact of Caring on Health and Education

Abstract: Research has shown that young people who care for parents and relatives (young carers and young adult carers) are at greater risk of mental and emotional difficulties and are more likely to do badly at school or college. To explore the difficulties faced by young adult carers (aged 14–25) in the UK, an online survey was conducted. Almost half (45%) of the 295 respondents reported having a mental health problem. The relationship between the extent of caring and perceived mental health problems and the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 13 publications
(13 reference statements)
3
88
1
3
Order By: Relevance
“…The government acknowledged in their recent carers action plan (Department of Health and Social Care, ) that young carers can suffer with poorer health and well‐being and often miss out on education and training opportunities. There is some evidence that caring is statistically associated with lower well‐being (Lloyd, ), worry (Nagl‐Cupal, Daniel, Koller, & Mayer, ), more frequent depressive states (Joseph et al, ), and absence from education (Becker & Sempik, ). A prevalence of 7% would suggest that the effects of caring may have serious and widespread deleterious effects personally and socially.…”
Section: Discussionmentioning
confidence: 99%
“…The government acknowledged in their recent carers action plan (Department of Health and Social Care, ) that young carers can suffer with poorer health and well‐being and often miss out on education and training opportunities. There is some evidence that caring is statistically associated with lower well‐being (Lloyd, ), worry (Nagl‐Cupal, Daniel, Koller, & Mayer, ), more frequent depressive states (Joseph et al, ), and absence from education (Becker & Sempik, ). A prevalence of 7% would suggest that the effects of caring may have serious and widespread deleterious effects personally and socially.…”
Section: Discussionmentioning
confidence: 99%
“…This makes it useful for assessment purposes when used by social workers and health professionals. It has been increasingly used as a survey instrument across different cultures, including the United Kingdom (e.g., Becker and Sempik 2018), Sweden (e.g., Järkestig-Berggren et al 2018), and Switzerland (e.g., .…”
Section: Ethics Of Developing the Quality Of Methodologymentioning
confidence: 99%
“…Other studies have tested for statistical association between the extent of caring and problems. Such studies are rare and show mixed findings, with some reporting that greater caring activity is associated with psychological problems (i.e., Joseph et al 2009a;Nagl-Cupal et al 2014) but not in others (i.e., Kavanaugh 2014;Becker and Sempik 2018;). Correlation does not however imply causality…”
Section: Prevalence and Effects Of Caringmentioning
confidence: 99%
“…Gender has been examined in some studied with children and adolescent with care responsibilities, reporting mixed findings. Some studies indicate that girls assume more caregiving tasks than boys (Nagl-Cupal et al, 2014;Becker and Sempik, 2018;Leu et al, 2018), whereas other studies, including both young carers below 18 years and YACs, have found higher prevalence of male caregivers (Levine et al, 2005;Pakenham and Cox, 2015). Evidently, more research on the relationship between gender and caring responsibility in YACs is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Young adult carers (YACs) are defined as individuals between 18 and 25 years who provide informal care, support or assistance to family members with disability, chronic illness, mental health issues, or substance misuse problems (Becker and Becker, 2008;Day, 2015). YACs are assumed to carry out substantial caring tasks, and to take on a significant level of responsibility (Becker and Sempik, 2018). The tasks performed may be practical, including household tasks (e.g., cooking, cleaning), emotional care (e.g., supporting, supervising), practical support (e.g., paying bills, administer medication), or personal care (e.g., washing, bathing, and dressing) (Becker and Becker, 2008).…”
Section: Introductionmentioning
confidence: 99%